Bangladesh : Fifth and Sixth Reviews Under the Extended Credit Facility Arrangement-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Bangladesh's Fifth and Sixth Reviews Under the Extended Credit Facility Arrangement. The current ECF arrangement, approved in April 2012, is drawing to a close. Over its three years, macroeconomic stability has been buttressed: growth is strong, inflation has eased, the public debt-to-GDP ratio has remained stable, and foreign reserves remain adequate. Progress on revenue mobilization, however, has been weak. Political uncertainty remains a key risk to the outlook. All performance criteria for the combined reviews have been met, all prior actions have been completed, and macroeconomic stability has been maintained. The IMF staff recommends completion of the combined reviews.